Two new species of Luisia (Vandeae, Orchidaceae) from the Andaman and Nicobar Islands, India - Mishra, Sanjay; Jalal, Jeewan Singh; Paulose, Vivek Chundakkattil; Singh, Lal Ji (Phytotaxa, 2020)
The Andaman and Nicobar Islands are the largest archipelago system in the Bay of Bengal, consisting of 572 islands and islets. Being situated between two major biodiversity hotspots, namely the Indo-Burma and Sundaland Biodiversity Hotspots, endows it with an unmatched distribution of plants with representatives of the Indian, Myanmar, Malaysian and Indonesian floras (Balakrishnan & Ellis 1996). Nearly 2100 species of angiosperms have been reported from the islands, of which about 11% are strictly endemic (Balakrishnan & Ellis 1996). As these islands are situated in the Equatorial belt and are exposed to marine impacts having a warm and humid tropical climate, the entire area is suitable for growth of orchids. The Andaman and Nicobar Islands harbour about 158 species of orchids, of which 23 species are endemic (Karthigeyan et al. 2014, Singh et al. 2019).